JESUS CHRIST AND HUMAN RIGHTS (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The coronavirus pandemic highlighted both the sacrifice of some to save human lives, but unfortunately also highlighted a cruel reality: selective medical treatment, argued by the fact that the medical staff was overwhelmed by the situation. The crises in Syria or Afghanistan have upset the international community, which has proved unprepared for the wave of refugees. Against the background of terrorism originating in these areas, the prejudices were those that marked some communities, making them unable to react to the need for security of refugees.